2009
DOI: 10.2215/cjn.00510109
|View full text |Cite
|
Sign up to set email alerts
|

Is Maximum Conservative Management an Equivalent Treatment Option to Dialysis for Elderly Patients with Significant Comorbid Disease?

Abstract: Background and objectives: There is ongoing growth of elderly populations with ESRD in Western Europe and North America. In our center, we offer an alternative care pathway of 'maximum conservative management' (MCM) to patients who elect not to start dialysis, often because of a heavy burden of comorbid illness and advanced age. The objective of our study was to compare clinical outcomes for patients who had ESRD and chose either MCM or renal replacement therapy (RRT).Design, setting, participants, & measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
389
1
17

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(413 citation statements)
references
References 43 publications
6
389
1
17
Order By: Relevance
“…Carson et al, using similar methods in patients older than 70 years, found median survival durations of 13.9 months in CKM patients and 37.8 months in dialysis patients (9). CKM patients were older but had similar comorbidity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Carson et al, using similar methods in patients older than 70 years, found median survival durations of 13.9 months in CKM patients and 37.8 months in dialysis patients (9). CKM patients were older but had similar comorbidity.…”
Section: Discussionmentioning
confidence: 97%
“…Most studies of patient survival in CKM imply that in elderly dependent patients with high comorbidity, dialysis confers only a small survival advantage, overall (5,6) or in terms of hospital-free days (9). Women have a better prognosis on CKM than men, and older patients than younger (10).…”
Section: Introductionmentioning
confidence: 99%
“…Starting dialysis was associated with a substantial and sustained decline in functional status among nursing home residents (3), and RRT may not be beneficial in the context of increasing frailty and loss of independence (4)(5)(6). A conservative care pathway is increasingly recognized as an alternative treatment to dialysis and has been introduced in the United Kingdom (UK) (1,(6)(7)(8)(9)(10), Australia (11,12), other European countries (13)(14)(15), and Asia (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…For example, nephrology literature highlights similar themes with older adults facing decisions about dialysis and kidney transplantation. [51][52][53][54][55][56] The incidence of end stage renal disease is increasing more quickly among older adults than any other age group and is associated with a low QOL and high mortality. 51 Given this trend, nephrology practice guidelines were developed to promote patients' active participation in the decision-making process.…”
Section: Older Patients With Other Diseases: Decision Making In Nephrmentioning
confidence: 99%